The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4236/aim.2012.24052
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Root Lesion Nematode: Identification and Plant Resistance

Abstract: Root lesion nematode, one of the three most devastated plant parasitic nematodes, is widespread in the world. They can invade various food and cash crops, and cause great agriculture loss. Recognition and identification of root lesion nematode are important joint of nematode management, as well as the mechanism research of plant anti-nematode, which is of great benefit to breed resistance varieties. In this review, the recent advances in nematode identification and research of plant anti-nematode are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
(35 reference statements)
0
17
0
5
Order By: Relevance
“…However, intraspecific variability in Pratylenchus spp. has been pointed out as one of the main difficulties in the taxonomy of this group since most of the characters used for identifying the species are very variable (YU et al, 2012;MOKRINI et al, 2013;NORONHA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, intraspecific variability in Pratylenchus spp. has been pointed out as one of the main difficulties in the taxonomy of this group since most of the characters used for identifying the species are very variable (YU et al, 2012;MOKRINI et al, 2013;NORONHA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…identification is needed. DNA-based techniques have been used previously to discriminate species of plant-parasitic nematodes (Oliveira et al 2011;Yu et al 2012). Pinochet et al (1994) reported the use of random amplified polymorphic DNA polymerase chain reaction (PCR) analysis to differentiate isolates of P. vulnus.…”
mentioning
confidence: 99%
“…Recently, ramie leaves and shoots have also been used as fodder for beef cattle and geese because of the plant’s high crude protein content [ 21 ]. Root lesion disease (RLD), a destructive root disease that is caused by the nematode Pratylenchus coffeae , severely impairs the growth and yield of ramie [ 22 ]. The lack of knowledge on ramie RLD resistance mechanisms or genes severely hinders efforts in effectively breeding and utilizing nematode-resistant ramie.…”
Section: Introductionmentioning
confidence: 99%